Luster [compact disc, unabridged] - Leilani, Raven (Macmillan Audio, 2020)
Edie is stumbling her way through her twenties, sharing a subpar apartment in Bushwick, clocking in and out of her admin job, making a series of inappropriate sexual choices. She is also haltingly, fitfully giving heat and air to the art that simmers inside her. And then she meets Eric, a digital archivist with a family in New Jersey, including an autopsist wife who has agreed to an open marriage, with rules. As if navigating the constantly shifting landscapes of contemporary sexual manners and racial politics weren't hard enough, Edie finds herself unemployed and invited into Eric's family life, though not by Eric. She becomes a hesitant ally to his wife and a de facto role model to his adopted daughter. Edie may be the only black woman young Akila may know.